Exploring and applying genes to enhance the resistance to Fusarium head blight in wheat - Ma, Haigang; Liu, Yongjiang; Zhao, Xueyan; Zhang, Suhong; Ma, Hongxiang (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB) is a destructive disease in wheat worldwide. Fusarium graminearum species complex (FGSC) is the main causal pathogen causing severe damage to wheat with reduction in both grain yield and quality. Additionally, mycotoxins produced by the FHB pathogens are hazardous to the health of human and livestock. Large numbers of genes conferring FHB resistance to date have been characterized from wheat and its relatives, and some of them have been widely used in breeding and significantly improved the resistance to FHB in wheat. However, the disease spreads rapidly and has been severe due to the climate and cropping system changes in last decade. It is an urgent necessity to explore and apply more genes related to FHB resistant for wheat breeding. In this review, we summarized the genes with FHB resistance and mycotoxin detoxication identified from common wheat and its relatives by using forward- and reverse-genetic approaches, introduced effects of such genes and the genes with FHB resistant from other plant species, and host induced gene silencing (HIGS) in enhancing the resistance to FHB in wheat. We also outlined the molecular rationale of the resistance and the application of the cloned genes for FHB control. Finally, we discussed the future challenges and opportunities in this field.